Correction to: The RESIST Senior Individuals Cohort: Design, participant characteristics and aims - Lennart Matthias Roesner; Manoj Kumar Gupta; Verena Kopfnagel; Nienke van Unen; Yvonne Kemmling; Jana‑Kristin Heise; Stephanie Castell; Xun Jiang; Lennart Riemann; Stephan Traidl; Berit Lange; Kurt‑Wolfram Sühs; et al. (GeroScience, 2024)

The RESIST Senior Individuals Cohort: Design, participant characteristics and aims - Lennart Matthias Roesner; Manoj Kumar Gupta; Verena Kopfnagel; Nienke van Unen; Yvonne Kemmling; Jana-Kristin Heise; Stephanie Castell; Xun Jiang; Lennart Riemann; Stephan Traidl; Berit Lange; Kurt-Wolfram Sühs; et al. (GeroScience, 2024)
The number of older adults worldwide is growing exponentially. However, while living longer, older individuals are more susceptible to both non-infectious and infectious diseases, at least in part due to alterations of the immune system. Here, we report on a prospective cohort study investigating the influence of age on immune responses and susceptibility to infection. The RESIST Senior Individuals (SI) cohort was established as a general population cohort with a focus on the elderly, enrolling an age- and sex-stratified sample of 650 individuals ( n = 100 20-39y, n = 550 61-94y, 2019–2023, Hannover, Germany). It includes clinical, demographic, and lifestyle data and also extensive biomaterial sampling. Initial insights indicate that the SI cohort exhibits characteristics of the aging immune system and the associated susceptibility to infection, thereby providing a suitable platform for the decoding of age-related alterations of the immune system and unraveling the molecular mechanisms underlying the impaired immune responsiveness in aging populations by exploring comprehensive, unbiased multi-omics datasets.